Land market responses to weather shocks: Evidence from rural Uganda and Kenya - Tabetando, Rayner; Fani, Djomo Choumbou Raoul; Ragasa, Catherine; Michuda, Aleksandr (Oxford University Press, 2023)
This study explores the responses of rural land markets to rainfall shocks in Uganda and Kenya. This study matches the panel data on farm households with rainfall shocks constructed using high-resolution precipitation and temperature data. In both countries, access to credit plays a key role in defining households’ land market responses to rainfall shocks. Households with access to credit respond to rainfall shocks by acquiring more farmland through increased participation in land rental and sales markets. Pathway analyses suggest that exposure to rainfall shock has an impact on land rental prices. There is some evidence that similar to grain reserves and livestock, land markets can provide an avenue for households to respond to rainfall shocks.